Representation of the Librarian in the Character of Urano Motosu in the Anime Ascendance af a Bookworm - Meilinda, Eka; Prasetyawan, Yanuar Yoga (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Purpose Research. The librarian profession has often been underestimated. Several studies regarding the media that represents librarians depict the profession negatively. Positive representation is needed to depict the ideal figure of a librarian to reduce the developing negative stereotypes of librarians. This research aims to identify the representation of librarians in the character Myne (Urano Motosu), the main character with a high librarian spirit who carries out her duties as a church librarian. Research Methods. The research method used is Roland Barthes' semiotics. Result.  This research shows that Myne's appearance as a librarian uses a vintage style, no glasses, and half-space bun hair. Myne is described as having a superior character as a librarian and can represent the ideal librarian figure. Myne's librarian's weakness is that she has low social experience. However, over time, he was able to adapt and finally eliminate these shortcomings.  Conclusions. Myne represents the ideal librarian so that librarians and librarian professional organizations can use her as a role model. Keywords: Representation; librarian; semiotics; anime